“Because at school, you can become somebody”: the perceived health and economic returns on secondary schooling in rural Burkina Faso - Werner, Luisa K.; Jabbarian, Jan; Kagoné, Moubassira; McMahon-Rössle, Shannon A.; Lemp, Julia M.; Souares-Coutant, Aurélia; Fink, Guenther; De Neve, Jan-Walter (PLOS ONE, 2019)
Background The perceived returns on schooling are critical in schooling decision-making but are not well understood. This study examines the perceived returns on secondary schooling in Burkina Faso, where secondary school completion is among the lowest globally (<10%). Methods We conducted a two-staged qualitative study using semi-structured interviews (N = 49). In the first stage, we sampled students, dropouts, parents and teachers from a random sample of five schools (n = 39). In the second stage, we interviewed key informants knowledgeable of the school context using snowball sampling (n = 10). Systematic analysis was based on a grounded theory approach with a reading of transcripts, followed by coding of the narratives in NVivo 12. Results Respondents nearly universally perceived health benefits to schooling. In particular, key health benefits included improved sexual and reproductive health outcomes, hygiene knowledge and practices, as well as better interactions with the formal health system. Common economic returns on schooling included improved employment opportunities and the provision of support to family members, in addition to generally attaining success and recognition. Indirect and long-term health returns, however, were infrequently mentioned by respondents. Conclusions While respondents reported nearly universally short-term health benefits to schooling, responses with regard to economic as well as indirect and long-term health benefits were more ambiguous. Future intervention studies on the perceived returns on formal education are needed to inform policy and reach education and health targets in the region.